Synthesis of Dual-Band Bandpass Filters With Short-Circuited Multiconductor Transmission Lines and Shunt Open Stubs - Sánchez-Martínez, Juan José; Pérez-Escribano, Mario; Márquez-Segura, Enrique (IEEE, 2019)
The design of dual-band bandpass filters consisting of series short-circuited wire-bonded multiconductor transmission lines and shunt open stubs is thoroughly carried out in this paper. Two different configurations are studied, and closed-form analytical design equations are derived to synthesize Chebyshev f iltering functions. A novel, simplified, and time-saving synthesis procedure to design dual-band filters with narrow or moderate broad bandwidths is finally presented, attending to the required final specifications and the physical and manufacturing limitations. The usefulness and validity of the proposed analytical equations are illustrated by designing, manufacturing, and measuring three different prototypes, showing an excellent agreement between analytical and measured results.
Keywords: Líneas de transmisión; Chebyshev, Sistemas de; Filtros de paso de banda; Bandpass filter; Chebyshev response; Coupled lines; Dual-band; Multiconductor transmission lines (MTLs); Shunt stubs